Medical Abortion Versus Manual Vacuum Aspiration in a Hilly District Hospital of Eastern Nepal: A Comparative Study - Panta, OB; Bhattarai, D; Parajuli, N (Kathmandu University Medical Journal, 2015)
Backgroud Nepal government has approved medical abortion and manual vacuum aspiration for early first trimester pregnancy. Both the procedures have been approved by World Health Organization for use in early first trimester. Objectives The study aims to compare efficacy and safety of medical abortion with surgical abortion in a district hospital of rural eastern Nepal. Method An observational study conducted in district hospital, dhankuta from July 2010 to January 2011. Clients for abortion services were counseled about methods of abortion and were allowed to make decision on their own and classified as medical abortion group (N=48) (receiving 200milligram Mifepristone followed by 800 microgram misoprostol sublingually or vaginally on day two)and manual vacuum aspiration group (N=36). The two groups were compared for rate of complete abortion and other complications and contraception use after procedure. Results Rate of complete abortion was similar in both groups, 95.8% among medical abortion and 97.2% in manual vacuum aspiration. Moderate to severe expulsion bleeding was reported in 91.6% of cases after Medical Abortion but none required medical attention for hemorrhage. Condom was the most preferred contraceptive in medical abortion group and depo provera in manual vacuum aspiration group. Conclusion Medical method of abortion using mifepristone and misoprostol is equally safe and effective as manual vacuum aspiration in rural setting district hospitals of Nepal. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12505 Kathmandu Univ Med J 2013; 43(3):206-209